Cultural Concern under Trade and Investment Agreements: Does it Really Work? - Widiatedja, I Gusti Ngurah Parikesit (Brawijaya Law Journal, 2018)
There has been a concern over the adverse influence of globalisation on local culture. Trade and investment agreements have included cultural concern in their provisions.Â  Employing these provisions, countries initiated trade and investment-related measures to secure what they have presumed as cultural traditions and values. This article seeks to examine if the incorporation of cultural concern under trade and investment agreement is effective to reconcile the need for securing culture and the spirit of free trade and free flows of investment. This article is normative research, examining the existing cultural concern under trade and investment agreements, cultural-related measures of particular countries, and how the judicial bodies have responded these measures in their decisions. This article argues that the incorporation of cultural concern has triggered a wide range of cultural-related measures. Nevertheless, the decision of judicial bodies, to some extent, has been effective to shield the purpose of cultural concern, especially to avoid disguise or inefficient protectionism, and to admit the right of countries to protect or promote their cultural traditions and values.